2008
DOI: 10.1016/j.apsusc.2008.05.082
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative ToF-SIMS studies of protein drug release from biodegradable polymer drug delivery membranes

Abstract: Biodegradable polymers are of interest in developing strategies to control protein drug delivery. The protein that was used in this study is Keratinocyte Growth Factor (KGF) which is a protein involved in the re-epithelialization process. The protein is stabilized in the biodegradable polymer matrix during formulation and over the course of polymer degradation with the use of an ionic surfactant Aerosol-OT (AOT) which will encapsulate the protein in an aqueous environment. The release kinetics of the protein f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…(Note: There are four tryptophan residues in KGF (http://ca.expasy.org/sprot/)). These films were also analyzed by ToF‐SIMS to determine the accumulation of AOT to the surface of the polymer, the results of this study was found by Burns and Gardella 21…”
Section: Methodsmentioning
confidence: 71%
See 1 more Smart Citation
“…(Note: There are four tryptophan residues in KGF (http://ca.expasy.org/sprot/)). These films were also analyzed by ToF‐SIMS to determine the accumulation of AOT to the surface of the polymer, the results of this study was found by Burns and Gardella 21…”
Section: Methodsmentioning
confidence: 71%
“…ToF SIMS was used to learn the extent of AOT removal in the material, balancing with the potential degradation of the PLLA and PLGA during the washing treatments. As in previous work, CN and OCN were used to track protein distribution within the membrane 21. The instrument that was used in this study is equipped with a C 60 polyatomic ion source that can be operated as a sputtering gun during depth profile analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Then, the wafers were frozen quickly. The two wafers were brushed aside vertically (freeze fracture) in liquid nitrogen and dried by freeze‐dryer vacuum. The frozen‐dried samples were used for TOF‐SIMS analysis.…”
Section: Methodsmentioning
confidence: 99%
“…[4][5][6] Hydrogels for biomaterial-based delivery allow for localized, controlled, and extended delivery. [7][8][9][10][11] Upon traumatic injury, the epithelium initiates an intraepithelial repair process which involves the expression of mitogenic and motogenic proteins such as KGF. 11 Prior work from our labs and other labs has shown that exogenous addition of KGF in in vitro and in vivo wound models can expedite the wound closure process.…”
Section: Introductionmentioning
confidence: 99%